Humoral immune response to mycobacterial heat shock protein (hsp)65 in the cerebrospinal fluid of neuro-Behcet patients - DİRESKENELİ, RAFİ HANER (BLACKWELL SCIENCE LTD, 2001)
Although systemic immune reactivity to 65-kD mycobacterial hsp65 (m-hsp65) has been shown previously in Behcet's disease (BD), local immune response was not investigated. Mie studied anti-m-hsp65 IgG, IgM and IgA antibodies in the serum and cerebrospinal fluid (CSF) of 25 ED patients with cerebral parenchymal involvement (p-NBD), seven ED patients with intracranial hypertension (ih-NBD), eight BD patients without central nervous system (CNS) involvement, 30 patients with multiple sclerosis (MS) and 24 patients with non-inflammatory CNS disorders (NIC). Significantly higher CSF IgG responses were detected in p-NBD patients (ELISA ratio 1.3 +/- 0.9) compared with NIC (0.7 +/- 0.4, P < 0.01). In p-NBD patients' IgG, IgM or IgA CSF anti-m-hsp65 positivity rate was 48% (12/25); this was significantly higher when compared with MS (3/30; P < 0.03) and NIC (3/24; P < 0.01). CSF anti-m-hsp65 IgG ratios correlated with the duration of ED (r = 0.4, P < 0.04) but not with the duration of neurological involvement. Serum IBM and IgA responses were elevated in ih-NBD, suggesting a different type of involvement than p-NBD. These results implicate an increased local humoral response to m-hsp65 in the CSF of p-NBD patients, which might be related to the pathogenesis of neurological involvement.
Keywords: neuro-Behcet's disease; cerebrospinal fluid; heat shock protein 65; T-CELLS; MULTIPLE-SCLEROSIS; DISEASE; ANTIBODIES; EXPRESSION; INVOLVEMENT; RECEPTOR; EPITOPE; ANTIGEN; BLOOD